Theoretical investigation of novel carbazole-fluorene based D-π-A conjugated organic dyes as dye-sensitizer in dye-sensitized solar cells (DSCs) - Thanisorn Yakhanthip (2018)
The ground state structure and frontier molecular orbital of newly synthesized carbazole-fluorene based D-π-A organic dyes, CFP1A, CFP2A, CFP1CA, and CFP2CA, were theoretically investigated using density functional theory (DFT) at B3LYP/6-31G(d,p) level. These dye molecules have been constructed based on carbazole-fluorene as the electron-donating moiety while introducing benzene units as π-spacer connected to different anchor groups, such as acrylic acid and cyanoacrylic acid, as acceptors. The electronic vertical excitation energies and absorption wavelength were carried out using time-dependent DFT (TD-DFT). Furthermore, the adsorptions of phenylacrylic acid and phenylcyanoacrylic acid on the TiO2anatase (101) surface were carried out by means of quantum-chemical periodic calculations employing periodic PBE functional with DNP basis set. The results promise that anchor dyes with strong withdrawing CN group have easier injected electron to the conduction band of semiconductor implying that CFP1CA and CFP2CA show better performance among four dyes. Additionally, the intramolecular charge transfers (ICT) from electron donor group to anchoring group of CFP1CA and CFP2CA have shown better performance. The calculated results provide the efficiency trend of our new dyes as CFP1CA ≈ CFP2CA > CFP1A ≈ CFP2A which are excellently agree with experimental observation. © 2011 Wiley Periodicals, Inc.